Assessment of Water Repellent Treatments for the Stone of the Matera Cathedral Facade (Italy). Issue 3 (4th March 2022) - Sacchi, Barbara; Vettori, Silvia; Andreotti, Alessia; Rampazzi, Laura; Colombini, Maria Perla; Tiano, Piero
ABSTRACT: After the cleaning procedures carried out during a recent restoration work, the Matera Cathedral's (UNESCO World Heritage Site) façade needed the application of a water repellent treatment. Aqueous emulsions of silanes/siloxanes, also in a mixture with acrylic polymer and an alkyl/alkoxysilanic resin (by BEL CHIMICA S.r.l. and PHASE restauro S.r.l), have been tested as representative of the most used formulations in the restoration of buildings in Italy, especially in the last decade. This paper focuses on the best practices to be adopted for the identification of the suitable protective product in terms of effectiveness, harmfulness and durability, in particular respect to photo-aging and thermo-hygrometrical aging. The conservation materials have been tested in situ and in laboratory on a stone block expressly extracted from the monument. The chemical composition of the products and their degradation processes were characterized by means of FT-IR and PY-GC-MS. The performance of the treatments was evaluated, both in laboratory by permeability, color and capillarity measurements and in situ by non-destructive techniques (IR reflectance spectroscopy, color measurements, water absorption tests by contact sponge). Silane/siloxane emulsion presented more pronounced degradation phenomena after artificial aging, while the mixture of silanes/siloxanes and acrylic polymers decreased the permeability to water vapour.